Factors Influencing the Implementation of Early Initiation of Breastfeeding in Newborns: A Literature Review - Kurniati Devi Purnamasari; Widya Maya Ningrum; Adhelia Dwi Lestari (Universitas Galuh, 2025)
Early Initiation of Breastfeeding (EIBF) is the process where a newborn begins breastfeeding within the first hour after birth through skin-to-skin contact between the mother and baby. The implementation of EIBF is an important intervention to reduce neonatal mortality and increase exclusive breastfeeding success. However, the implementation of EIBF is still not optimal in various health facilities. This study aims to identify factors influencing the implementation of Early Initiation of Breastfeeding in newborns based on previous research findings. The method used was a literature review by analyzing scientific articles obtained from Google Scholar, PubMed, and ScienceDirect databases published within the last 10 years. Articles were selected based on inclusion criteria relevant to the research topic. The results of the review show that factors influencing the implementation of EIBF include maternal knowledge, maternal attitudes toward breastfeeding, support from health workers, family support, mode of delivery, and health facility policies. In conclusion, the success of EIBF implementation is influenced by individual factors, health worker support, and health service system factors. Therefore, increased maternal education and strong support from health workers are needed to improve EIBF implementation.